Allelopathic effect of argemone mexicana L. On germination and seedling growth characteristics of lentil (lens culinaris) (Journal of Bio-Science, 2011)
DOI: http://dx.doi.org/10.3329/jbs.v18i0.8791JBS 2010; 18(0): 146-147